Antihypertensive drugs and brain function: mechanisms underlying therapeutically beneficial and harmful neuropsychiatric effects. Issue 3 (28th July 2022) - Carnovale, Carla; Perrotta, Cristiana; Baldelli, Sara; Cattaneo, Dario; Montrasio, Cristina; Barbieri, Silvia S; Pompilio, Giulio; Vantaggiato, Chiara; Clementi, Emilio; Pozzi, Marco
Abstract: A bidirectional relationship exists between hypertension and psychiatric disorders, including unipolar and bipolar depression, anxiety, post-traumatic stress disorder (PTSD), psychosis, schizophrenia, mania, and dementia/cognitive decline. Repurposing of antihypertensive drugs to treat mental disorders is thus being explored. A systematic knowledge of the mechanisms of action and clinical consequences of the use of antihypertensive agents on neuropsychiatric functions has not been achieved yet. In this article, we review the putative role of antihypertensive agents in psychiatric disorders, discuss the targets and mechanisms of action, and examine how and to what extent specific drug classes/molecules may trigger, worsen, or mitigate psychiatric symptoms. In addition, we review pharmacokinetics (brain penetration of drugs) and pharmacogenetics data that add important information to assess risks and benefits of antihypertensive drugs in neuropsychiatric settings. The scientific literature shows robust evidence of a positive effect of α1 blockers on PTSD symptoms, nightmares and sleep quality, α2 agonists on core symptoms, executive function, and quality of life in Attention-Deficit/Hyperactivity Disorder, PTSD, Tourette's syndrome, and β blockers on anxiety, aggression, working memory, and social communication. Renin-angiotensin system modulators exert protective effects on cognition, depression, and anxiety, and the loop diuretic bumetanide reduced the core symptoms of autism in a subset of patients. There is no evidence of clear benefits of calcium channel blockers in mood disorders in the scientific literature. These findings are mainly from preclinical studies; clinical data are still insufficient or of anecdotal nature and seldom systematic. The information herewith provided can support a better therapeutic approach to hypertension, tailored to patients with, or with high susceptibility to, psychiatric illness. It may prompt clinical studies exploring the potential benefit of antihypertensive drugs in selected patients with neuropsychiatric comorbidities that include outcomes of neuropsychiatric interest and specifically assess undesirable effects or interactions. Graphical Abstract: Graphical abstract